Transvenous lead extraction of cardiac implantable electronic devices, Indications, results and complications - Ibrahim Abdelhakam Aly Elzoghby; Hassan Mohamed Khaled; Khaled Hussein Mohamed; Mahmoud Mohamed Kenawy (Cairo : Ibrahim Abdel Hakam Aly Elzoghby, 2018)
Background: Lead extraction is by far a complex procedure as it carries some risks for the patient. Clear indications, expertly trained personnel, adequate tools, and appropriate environment and facilities are mandatory for its safe removal.When considering indications for lead extraction, whatever they be, it is important first to evaluate the strength of the indication and the risks of the intervention on an individualized patient basis. Thereafter, the risk/benefit ratio of each patient should be balanced with the level of experience of the operator. Objective: to present and analyze the first experience of Critical Care Department in Cairo University in the patients who were referred for percutaneous lead extraction as regards indications, results,outcome and complications. Patients and methods: a prospective study conducted from March 2016 till December 2017.Twenty consecutive patients were included for permanent pace maker and defibrillator percutaneous lead extraction.Transvenous lead extraction was done according to the Heart Rhyhtm Society (HRS) indications (2009) for lead extraction class I & II e.g. infections, non-functional leads, lead vegetations ,thrombosis and venous stenosis. All Patients were subjected to full history taking, clinical examination and investigations then the procedure of extraction was done according to specific protocol involving proper environment, personnel and techniques
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Criical Care Medicine
Issued also as CD
Keywords: Cardiac implantable electronic devices; Heart Rhyhtm Society (HRS); Lead extraction